2020
DOI: 10.1088/1742-6596/1519/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Parameters on Joining Dissimilar Low Carbon Steel and 3CR12 Ferritic Stainless Steel by GTAW with ER308L Filler Metal

Abstract: The effect of welding parameters on GTAW (gas tungsten arc welding) between low carbon steel and 3CR12 ferritic stainless steel with ER308L filler metal was investigated with regard to microstructure and mechanical properties. The welded metal presented good configuration. The microstructure of weldment was found to be of widmanstatten austenite, acicular ferrite and martensite. Martensite and Cr-rich carbide precipitated particles formed under certain conditions in weldment produced results of both better har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…From the macrographs in figures 5(a) and (b), the dilution can be calculated using equation (1). We found a dilution percentage of about 21%dilution for 70A-ER308L specimen and 23%dilution for 100A-ER308L specimen [26]. These correspond to normal dilution percentages with the previous theory of Lippoldand Kotecki [27].…”
Section: Materials and Experimental Proceduressupporting
confidence: 72%
See 1 more Smart Citation
“…From the macrographs in figures 5(a) and (b), the dilution can be calculated using equation (1). We found a dilution percentage of about 21%dilution for 70A-ER308L specimen and 23%dilution for 100A-ER308L specimen [26]. These correspond to normal dilution percentages with the previous theory of Lippoldand Kotecki [27].…”
Section: Materials and Experimental Proceduressupporting
confidence: 72%
“…Studies by Araújo et al [40] and Bansod et al [41] reported hardness values in the fusion zone with ER308L and 308 filler wires, which presented results similar to those verified in the present work. Hardness values of approximately 175, 182, and 180 HV of the 70A-ER308L fusion zone [26] were higher than those of the 70A-ER309L and 100A-ER309L fusion zones. According to the higher hardness of 70A-ER308L, the solid solution from both sides of the base metal diffused the interstitial solute atoms into a delta ferrite structure.…”
Section: Hardness and Tensile Propertiesmentioning
confidence: 66%